2008
DOI: 10.1097/hjh.0b013e328311ce04
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, awareness, treatment and control of hypertension in healthy unrelated male–female pairs of European regions: the dietary habit profile in European communities with different risk of myocardial infarction – the impact of migration as a model of gene–environment interaction project

Abstract: In communities of healthy unrelated male-female pairs from three different European regions, more than half of hypertensive patients appeared to have blood pressure levels not at target values. Interventions are required to optimize the use and effectiveness of antihypertensive drug therapy in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
24
2
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 30 publications
5
24
2
3
Order By: Relevance
“…[13][14][15] Moreover, the proportion of individuals with hypertension aware, treated and controlled was unacceptably low in urban Chinese. The results also showed that most hypertensive patients, whether unaware or aware of their hypertension diagnosis, did not think that high BP would endanger their lives.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] Moreover, the proportion of individuals with hypertension aware, treated and controlled was unacceptably low in urban Chinese. The results also showed that most hypertensive patients, whether unaware or aware of their hypertension diagnosis, did not think that high BP would endanger their lives.…”
Section: Discussionmentioning
confidence: 99%
“…There was no significant difference associated with age group or gender. These rates are between 15.2 and 47.7% in Europe, [20][21][22][23] 19.6% in Brazil, 24 3.9 and 30.6% in China [25][26][27] and 50.1% in the United States, as determined by the National Health and Nutrition Examination Survey 2007-2008. 28 The signs and symptoms presented on admission to the hospital vary according to the clinical presentation of HC, depending on which target organs are affected most severely.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on BP mean level or hypertension are less prone to such bias because: (i) BP elevations and hypertension are generally asymptomatic, and (ii) over 50% of individuals with high BP are unaware of their condition (216). Nevertheless, the healthy worker effect can occur in cross-sectional studies on hypertension and generally lead to an underestimation of the true effect (210).…”
Section: (Tables A-c)mentioning
confidence: 99%